2016
DOI: 10.1097/01.prs.0000479965.14775.f0
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial to Evaluate the Efficacy and Safety of Lidocaine-Containing Monophasic Hyaluronic Acid Filler for Nasolabial Folds

Abstract: Therapeutic, I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…This filler, developed by Medytox, is produced with distinct double cross-linking, called Stabilized Hyaluronic Acid & Purification Enhancement technology, which makes it highly cohesive. 13,14 The aim of this study was to compare the effectiveness and safety of Neuramis® Volume Lidocaine and VYC-20L for restoration of mid-face volume in Asians with moderate to severe MVD. Photographs of all subjects at each center were assessed by another independent blinded evaluator.…”
Section: Among Other Available Hyaluronic Acid Dermal Fillers Ismentioning
confidence: 99%
See 1 more Smart Citation
“…This filler, developed by Medytox, is produced with distinct double cross-linking, called Stabilized Hyaluronic Acid & Purification Enhancement technology, which makes it highly cohesive. 13,14 The aim of this study was to compare the effectiveness and safety of Neuramis® Volume Lidocaine and VYC-20L for restoration of mid-face volume in Asians with moderate to severe MVD. Photographs of all subjects at each center were assessed by another independent blinded evaluator.…”
Section: Among Other Available Hyaluronic Acid Dermal Fillers Ismentioning
confidence: 99%
“…Among other available hyaluronic acid dermal fillers is Neuramis® Volume Lidocaine (Medytox, Inc, Seoul, Republic of Korea), a 20 mg/mL monophasic hyaluronic acid filler that incorporates 0.3% lidocaine. This filler, developed by Medytox, is produced with distinct double cross‐linking, called Stabilized Hyaluronic Acid & Purification Enhancement technology, which makes it highly cohesive . The aim of this study was to compare the effectiveness and safety of Neuramis® Volume Lidocaine and VYC‐20L for restoration of mid‐face volume in Asians with moderate to severe MVD.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 12 , 13 , 16 , 19 , 31 , 33 External volume expansion has previously demonstrated an influence on histological structure of tissues, and has shown to increase adipogenic potential 10 , 17 in fat grafting, and potential utility in diabetic and radiation in small experimental animal models. 8 , 13 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…7 Hence, several randomized clinical studies have been conducted to evaluate the effectiveness and safety of lidocaine-containing HA filler for NLFs correction. [8][9][10] In this multicenter, double-blind, randomized controlled, splitface, clinical study, we tried to assess the effect on pain relief of HA with lidocaine, mainly focusing on a comparison of immediate and post-injection pain over the course of 1 hour in a group of Korean patients. We confirmed that 95% of patients reported reduced pain immediately after treatment.…”
Section: Discussionmentioning
confidence: 99%